Signifying the Relationship Between Psychological Factors and Turnover Intension: The Mediating Role of Work-Related Stress and Moderating Role of Job Satisfaction - Xue, Jinli; Wang, Hao; Chen, Meng; Ding, Xiujuan; Zhu, Mengting (Frontiers in Psychology, 2022)
Human capital plays a significant role in an organization’s advancement. In recent years, emerging work-related psychological issues have become a critical factor, demanding considerable attention from management. As such, this study measures the role of job satisfaction in work-related stress and employees' turnover intentions. There is a mediating relationship between work-related stress – such as emotional exhaustion, work engagement, role conflict, and psychosocial risks – and turnover intentions. The study used primary data collection techniques to gather data and purposive sampling to analyze the data. The study's sample size consists of 270 employees working in Chinese organizations. Smart PLS software was used to test the research hypothesis. The study results show the mediating role of work-related stress and moderating role of employees' job satisfaction. Accordingly, the study provides implications for managers, encouraging them to take the necessary steps in controlling the turnover rate by enhancing employees' morale (i.e., job satisfaction) and work engagement.